CORRUPTION AND THE REALISATION OF HUMAN RIGHTS: SOUTH SUDAN AND THE RIGHT TO EDUCATION LLICIT BUSINESS FORUMS IN SOUTH AFRICA: A SURVEY CORRUPTION AND THE REALISATION OF HUMAN RIGHTS: THE CASE OF SOUTH SUDAN AND THE RIGHT TO EDUCATION - Ongee Paito, Atel (Journal of Anti-Corruption Law, 2023)
The South Sudan Anti-Corruption Commission denounced corruption as something which hinders sustainable education. The debate on the relationship between corruption and human rights thus continues. In South Sudan, like many parts of the world, public and private sector leaders have illegally allocated resources for education and related projects, to personal gain. This article contends that corruption in South Sudan is an impediment to realising rights and it violates human rights. Drawing a link between corruption and human rights, as this article aims to do, enhances our understanding of corruption. This article seeks to bring a unique viewpoint by utilising human rights institutions and practices in combating the negative consequences of corruption on the realisation of human rights.